Develop effective decision making for remanufacturing automotive components - Abu, Mohd Yazid Bin (2019)
Remanufacturing is a process that returns the second-hand product that have the performance is similar or better that the new product. The remanufacturer cannot be predicting the end of life (EOL) of crankshaft to remanufacture, repair or reject due to the limited information provided by Original Equipment Manufacturer (OEM) which depend on a traditional inspection to make a decision. Subsequently, Traditional Cost Accounting (TCA) which the manufacturing overhead are driven by the production volume are being applied. The aim of this work is to develop a distinctive pattern of crankshaft and identify the critical and non-critical parameter of crankshaft based on the Mahalanobis Taguchi System (MTS), then applied the Activity Based Costing (ABC) as a method of estimation for the remanufacturing cost of crankshaft. In methodology, the scatter diagram is construct to develop the pattern recognition using T Method-3, Taguchi orthogonal array (OA) are applied to identify the important parameter using T Method and lastly, the ABC system is analysed the costing of critical parameters. Based on the MTS method, the EOL of crankshaft can be classified into 3 categories which are remanufacturable, rejected, and repairable. In this work, the MD of Mtu183 engine model were developed from 0.003165 to 0.005667 whereby for Man engine model were developed from 0.386108 to 2.004725. Hence, when apply Taguchi’s orthogonal array, it shows there are 2 critical and 4 non-critical of crankpin whereby Man has 3 critical and 3 non-critical crankpin diameters of crankshaft. Lastly, when ABC is integrated with MTS method, these combinations produce the cheaper price compared with ABC integrate with traditional cost. The cost of combination MTS method with ABC are Man (MYR738.13) and Mtu183 (MYR687.90) compare with ABC with traditional which are Man (MYR800.01) and Mtu183 (MYR754.37).